The Alexander Gold Coinage of Sidon - Taylor, Lloyd W. H. (KOINON: The International Journal of Classical Numismatic Studies, 2025)
This study examines the Alexander gold coinage of Sidon struck in the period 332-3051 and refutes Le Rider’s proposed reattribution of the earliest of these issues to Tarsos. It evinces that the first of Alexander’s gold coinage, an undated series with no identifying ethnic mint mark, was struck at Sidon under military administration during the eighteen months of military campaign that progressed from Tyre, to Gaza, and then to Egypt. The combined Macedonian, Cypriote and Phoenician fleets proved pivotal to success in this lengthy campaign, possibly providing an impetus for the adoption of the gold stater reverse design with its strong naval connotations. In 332/1 with the shift of the military campaign from Phoenicia into the Persian heartland, the responsibility for gold mintage passed to the satrapal administration of Southern Syria, later to be amalgamated into the satrapy of Syria by 329/8. These administrative changes are reflected in the evolution of mint marking practice of the different precious metal coinages at Sidon. Identified in the dated Sidon sequence is an undated stater issue that is die linked to the staters of regnal year 10 (324/3). Possibly, this issue was undated due to the political uncertainty that surrounded succession and regency following the death of Alexander the Great. This would explain the absence of a regnal year 11 (323/2) dated coinage and indicate that the dating era employed at Sidon was that of Alexander, rather than that of his appointed vassal. Conservatively estimated, the value of Sidon’s gold mintage struck in Alexander’s lifetime was seven times that of its silver issuance. In fact, Sidon’s output was of such magnitude that prior to 320 it was the preeminent issuer of gold coinage from the eastern mints of Alexander the Great.